Influence of a Nigerian honey on CYP3A4 biotransformation of quinine in healthy volunteers. (14th July 2015) - Igbinoba, S. I.; Akanmu, M. A.; Onyeji, C. O.; Soyinka, J. O.; Owolabi, A. R.; Nathaniel, T. I.; Pullela, S. V.; Cook, J. M.
Summary What is known and objectives Some studies, howbeit with conflicting reports, have suggested that consumption of honey has a potential to modulate drug metabolizing enzymes which may result in a honey–drug interaction. Numerous studies have established that honey varies in composition, influenced by the dominant floral, processing and environmental factors. Thus, variation in honey composition may be a contributing factor to the controversial results obtained. No previous drug interaction study has been carried out with any honey from Africa. CYP 3A4 is an important enzyme in drug metabolism studies as it is involved in the metabolism of over 50% of drugs in clinical use and quinine remains very relevant in malaria treatment in the tropics, and we therefore determined whether there is potential drug interaction between a Nigerian honey and quinine, a drug whose metabolism to 3‐hydroxyquinine is mediated majorly by CYP3A4. Methods In a three‐phase randomized crossover study with a washout period of 2 weeks between each treatment phase, ten (10) healthy volunteers received quinine sulphate tablet (600 mg single dose) alone (phase 1) or after administration of 10 ml of honey (Phase 2) and 20 mL of honey (Phase 3) twice daily for seven (7) days. Blood samples were collected at the 16th hour post‐quinine administration in each phase, and quinine and its major metabolite, 3‐hydroxyquinine, were analysed using a validated HPLC method. Results After scheduled doses of honey, the mean metabolic ratios of quinine (3‐hydroxyquinine/quinine) increased by 24·4% (with 10 mL of honey) and reduced by 23·9% (with 20 mL of honey) when compared to baseline. These magnitudes of alteration in the mean metabolic ratios were not significant (P > 0·05; Friedman test). The geometric mean (95% CI) for the metabolic ratio of quinine before and after honey intake at the two dose levels studied was 0·82 (0·54, 1·23) and 1·29 (0·96, 1·72), respectively, and were also not significant (P = 0·296 and 0·081 respectively; Student's t‐test). What is new and conclusion This is a pioneer study on the effect of Nigerian/African honey on quinine metabolism. The findings indicated that low and high doses of honey did not significantly affect metabolism of quinine to 3‐hydroxyquinine. This suggests that CYP3A4 activity is not significantly altered following low or high dose of honey, as CYP3A4 has been reported to be responsible for the conversion of quinine to 3‐hydroxyquinine. In conclusion, the outcome of this study suggests that there may be no potential significant metabolic interaction between Nigerian honey and quinine administration.